Modal analysis of the human tympanic membrane of middle ear using the finite-element method - Skrodzka, E.; Modławska, J. (Archives of Acoustics, 2006)
This paper provides a theoretical vibrations model of tympanic membrane constructed andsolved using the finite-element method. This method is an appropriate tool to analyze themiddle-ear vibrations because it enables modeling in details the complicated shape of themiddle-ear and, moreover, and allows to calculate the distribution of vibrations stimulated bysinusoidal signals. The number of the 3-dimensional tetrahedral elements was assumed to be591 and material properties used were based on data available in the literature. This modelhas a uniform density of $1.2 · 10^3$ kg/m$^3$, an area of $70· 10^{−6}$ m$^2$, a depth of $1.54 · 10^{−3}$ mat the umbo, a mean thickness of $1.32 · 10^{−4}$ m, and a Poisson’s ratio 0.3. Constrains wereaccomplished by two different springs, linear and torsional. The results obtained are comparedwith their counterparts scattered in the literature.